Evaluation of prescribing pattern and errors among elderly outpatients in Bangladesh by using AGS beers criteria - Mahmud, KM Fahim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.